PENGARUH BRAND IMAGE, BRAND AWARENEES, SERVICE QUALITY DAN DIGITAL BANKING TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING (STUDI PADA NASABAH BANK SYARIAH INDONESIA KCP UNGARAN DIPONEGORO) - dina irmawati (Program Studi Perbankan Syariah, 2025)
This study aims to determine how brand image, brand awareness, service quality and digital banking influence customer loyalty through customer satisfaction as an intervening variable of a case study on BSI Bank Customers KCP Ungaran Diponegoro 1. This study is a type of quantitative research using primary data and data collection instruments by filling out questionnaires. The sample taken was 100 respondents with a probability sampling technique of sampling type without replacement. The data obtained were then processed using the IBM SPSS version 21 analysis tool. The results of this study indicate that the brand image variable does not significantly affect customer loyalty. The brand awareness variable has a positive and significant effect on customer loyalty. Service quality does not significantly affect customer loyalty. Digital banking has a positive and significant effect on customer loyalty. Satisfaction has a positive and significant effect on customer loyalty. Satisfaction cannot mediate brand image on customer loyalty. Satisfaction can mediate brand awareness, service quality, and digital banking on customer loyalty.